2002
DOI: 10.1002/imhj.10004
|View full text |Cite
|
Sign up to set email alerts
|

Getting dads involved: Predictors of father involvement in Early Head Start and with their children

Abstract: Father characteristics and psychosocial functioning were examined as predictors of father involvement both with an Early Head Start (EHS) program and with their infant. Variables examined as potential predictors were selected based on the program's emphasis on building relationships as their primary intervention strategy. The 72 low-income fathers included in this study were predominantly Caucasian and married or living with their child's mother. Fathers' characteristics predicted their involvement in expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
2
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 39 publications
8
88
2
6
Order By: Relevance
“…105,130 In a study in families of children enrolled in Head Start, nondepressed fathers were more involved with infants than were depressed fathers. 131 Similarly, depressed fathers in the Fragile Families and Child Wellbeing Study reported less father-child activities (engagement and reciprocal play), lower levels of relationship quality with the mother, and lower levels of coparental relationship supportiveness than did nondepressed fathers. 132 Conflict in the coparental relationship may heighten the risk of the development of depression in fathers, 106,108,125 but more research is needed in this aspect of family life and paternal depression.…”
Section: Influence Of Fathers' Mental and Physical Well-being On Chilmentioning
confidence: 98%
“…105,130 In a study in families of children enrolled in Head Start, nondepressed fathers were more involved with infants than were depressed fathers. 131 Similarly, depressed fathers in the Fragile Families and Child Wellbeing Study reported less father-child activities (engagement and reciprocal play), lower levels of relationship quality with the mother, and lower levels of coparental relationship supportiveness than did nondepressed fathers. 132 Conflict in the coparental relationship may heighten the risk of the development of depression in fathers, 106,108,125 but more research is needed in this aspect of family life and paternal depression.…”
Section: Influence Of Fathers' Mental and Physical Well-being On Chilmentioning
confidence: 98%
“…Fathers play an important role in the development of children's self-regulation and social competence (McBride, Dyer, & Rane, 2008;Raikes, Summers, & Roggman, 2005;Roggman, Boyce, Cook, & Cook, 2002). Father involvement can be extremely beneficial to children's development (Berlyn et al, 2008;Fletcher, 2010;O'Brien, 2004).…”
Section: The Role Of Fathersmentioning
confidence: 99%
“…Father involvement can be extremely beneficial to children's development (Berlyn et al, 2008;Fletcher, 2010;O'Brien, 2004). Several studies evidence the positive impact of fathers on children's development in areas such as school readiness, pro-social behaviours and cognitive development (Fabiano, 2007;McBride et al, 2008;Raikes et al, 2005;Roggman et al, 2002). Some research suggests that fathers have a greater influence on a child's misbehaviours than mothers (Lundahl, Tollefson, Risser, & Lovejoy, 2008).…”
Section: The Role Of Fathersmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that depressed mothers are less sensitive towards their babies (Murray et al, 1996;Steadman et al, 2007), being more intrusive or withdrawn (Black et al, 2007;Field, Hernandez-Reif & Diego, 2006;Herrera, Reissland & Shephard, 2004;) and less accurate in interpreting their baby's emotions (Broth, Goodman, Hall & Raynor, 2004). Similarly paternal depression has been associated with a less optimal father -infant relationship (Field, Hossain & Malphurs, 1999;Field, 2010; for a review, see Wilson & Durbin, 2010) with examples of less involvement with their child (Roggman, Boyce, Cook & Cook, 2002). Also, maternal depression has been shown to indirectly influence the father-infant interaction negatively (Bradley & Slade, 2011;Goodman, 2008).…”
Section: Parental Mental Health and Parent-infant Interactionsmentioning
confidence: 99%